Exploring Education Peace in Islamic Boarding Schools: Local Wisdom as Forming the Character of Peace-Minded Students - Khoniq Nur Afiah; Lia Fadhliyah (IJIE International Journal of Islamic Education, 2022)
Peace education is generally held in formal education, whereas in non-formal education environments such as Islamic boarding school Complex R2, many have been born through their traditions. This study aims to examine the habits of the Al Munawwir Islamic Boarding School Complex R2 in implementing peace education in Islamic boarding schools. This research is essential to explore peace education so that it can add and prove the existence of pesantren treasures. The research approach used is descriptive-qualitative to analyze, interpret and conclude deductively-inductively as well as the dynamics of phenomena object relationships. The research data sources consist of primary data and secondary data. Preliminary data were obtained from key informants such as Kiai; secondary data came from data and documentation. Data were collected by observation and interviews. The study results show that peace education at the Al-Munawwir Islamic boarding school Complex R2 aims to form peace-loving students and is carried out through a variety of local activities, such as: 1) Study of the Islamic classic book with the theme of tolerance and justice, 2) Implementation of hubbul wathon (love of country) through the commemoration of national holidays, 3) Involvement of all santris (students) as activity organizing agents, and 4) Performance of democratic attitudes by caregiver